Do Children With Developmental Language Disorder Activate Scene Knowledge to Guide Visual Attention? Effect of Object-Scene Inconsistencies on Gaze Allocation - Helo, Andrea; Guerra, Ernesto; Coloma, Carmen Julia; Aravena-Bravo, Paulina; Rämä, Pia (Frontiers in Psychology, 2022)
Our visual environment is highly predictable in terms of where and in which locations objects can be found. Based on visual experience, children extract rules about visual scene configurations, allowing them to generate scene knowledge. Similarly, children extract the linguistic rules from relatively predictable linguistic contexts. It has been proposed that the capacity of extracting rules from both domains might share some underlying cognitive mechanisms. In the present study, we investigated the link between language and scene knowledge development. To do so, we assessed whether children with Developmental Language Disorder (DLD), who present several difficulties in the linguistic domain, are equally attracted to object-scene inconsistencies in a visual free-viewing task, in comparison with children with Typical Language Development (TLD). All children explored visual scenes containing semantic (e.g., soap on a breakfast table), syntactic (e.g., bread on the chair back), or both inconsistencies (e.g., soap on the chair back). Since scene knowledge interacts with image properties (i.e., saliency) to guide gaze allocation during visual exploration from the early stages of development, we also included the objects' saliency rank in the analysis. The results showed that children with DLD were less attracted to semantic and syntactic inconsistencies than children with TLD. In addition, saliency modulated syntactic effect only in the group of children with TLD. Our findings indicate that children with DLD do not activate scene knowledge to guide visual attention as efficiently as children with TLD, especially at the syntactic level, suggesting a link between scene knowledge and language development.